Therapeutic targeting of GSK3β enhances the Nrf2 antioxidant response and confers hepatic cytoprotection in hepatitis C. Issue 1 (8th May 2014) - Jiang, Yongfang; Bao, Hui; Ge, Yan; Tang, Wei; Cheng, Du; Luo, Kaizhong; Gong, Guozhong; Gong, Rujun
Abstract : Objective: Impaired adaptive response to oxidative injuries is a fundamental mechanism central to the pathogenesis of chronic hepatitis C (CHC). Glycogen synthase kinase (GSK) 3β is an indispensable regulator of the oxidative stress response. However, the exact role of GSK3β in CHC is uncertain and was examined. Design: GSK3β and Nrf2 signalling pathways were examined in JFH1 HCV infected Huh7.5.1 hepatocytes, and also in liver biopsy specimens from CHC patients. Results: HCV infection elicited prominent Nrf2 antioxidant response in hepatocytes, marked by elevated expression of the Nrf2-dependent molecule haem oxygenase-1 and subsequent protection from apoptotic cell death. Inhibitory phosphorylation of GSK3β seems to be essential and sufficient for HCV-induced Nrf2 response. Mechanistically, GSK3β associated and physically interacted with Nrf2 in hepatocytes. In silico analysis revealed that Nrf2 encompasses multiple GSK3β phosphorylation consensus motifs, denoting Nrf2 as a cognate substrate of GSK3β. In the presence of TGFβ1, the HCV-induced GSK3β phosphorylation was blunted via a protein phosphatase 1-dependent mechanism and the cytoprotective Nrf2 response drastically impaired. This effect was counteracted by lithium, a selective inhibitor of GSK3β. In liver biopsy specimens from CHC patients, the expression of phosphorylated GSK3β positively correlated with Nrf2 expression and was inversely associated with the degree of liver injury. Moreover, CHC patients who received long-term lithium carbonate therapy primarily for concomitant psychiatric disorders exhibited much less liver injury, associated with enhanced hepatic expression of Nrf2. Conclusions: Inhibition of GSK3β exerts hepatoprotection in CHC possibly through its direct regulation of Nrf2 antioxidant response.